Multinational companies and indigenous development: An empirical analysis - Holger Görg; Eric Strobl (Centre for Economic Policy Research (CEPR), 2002)
This Paper presents an empirical study of the effect of foreign multinational companies on the development of indigenous firms in the host country. Our starting point is a recent paper by Markusen and Venables (1999) that shows formally that multinationals, through the creation of linkages with indigenous suppliers, can exert positive effects on the development of indigenous firms. Based on the literature on entry in industrial organisation, we estimate empirically a model describing the entry of indigenous firms using data for the Irish manufacturing sector. Our results indicate that there is a positive effect of multinational companies on the entry of indigenous firms for a variety of alternative specifications.
Keywords: F23; L60; 330; Multinationales Unternehmen; Agglomerationseffekt; Unternehmensgründung; Verarbeitendes Gewerbe; Irland